Revising CX3CR1 Expression on Murine Classical and Non-classical Monocytes - Meghraoui-Kheddar, Aïda; Barthelemy, Sandrine; Boissonnas, Alexandre; Combadière, Christophe (Frontiers in Immunology, 2020)
In mice, monocytes (Mo) are conventionally described as CX3CR1low classical Mo (CMo) and CX3CR1high non-classical Mo (NCMo) based on the expression of EGFP in Cx3cr1+/EGFP mice and by analogy with human CX3CR1 expression. Although this terminology is widely used, it may not reflect the expression of CX3CR1 on Mo subsets. Using an unsupervised multiparametric analysis of blood Mo in steady state and after sterile peritonitis, we observed that CX3CR1 expression did not discriminate the CMo from the NCMo subsets. Our results highlight that despite being a reliable reporter to discriminate Mo subpopulations, EGFP level in Cx3cr1+/EGFP mice does not reflect CX3CR1 expression measured by a fluorescently-labeled CX3CL1 chemokine and a CX3CR1 specific antibody. In conclusion, authors should be cautious not to identify murine classical and non-classical Mo as CX3CR1low and CX3CR1high but rather use alternative markers such as the combination of Ly6C and CD43.